An unusual case of intradural intramedullary dorsal bronchogenic cyst in spine - Dusad, Tarun; Kundnani, Vishal; Dutta, Shumayou; Patel, Ankit; Mehta, Gaurav; Singh, Mahendra (Journal of Spine Surgery, 2017)
Bronchogenic cysts are congenital malformations derived from anomalous budding of the embryonic foregut. Intraspinal bronchogenic cysts are extremely rare and most of them are extramedullary. There has been only one case of intramedullary spinal bronchogenic cyst reported. We present an 18-year-old male patient with spastic paraparesis and bowel and bladder involvement. MRI revealed a 2 cm diameter intradural and intramedullary lesion at D2–D3 level which was hyperintense on T1 and hypointense on T2 imaging. Histopathological examination after surgical excision of the lesion revealed a bronchogenic cyst. To our knowledge this is the first case reporting an intramedullary bronchogenic cyst at the upper dorsal level and overall second reported case of intramedullary spinal bronchogenic cyst.